Two new species of Haliplus Latreille, 1802 (Coleoptera, Haliplidae) from Northern Brazil - Benetti, Cesar João; Hamada, Neusa (Zootaxa, 2017)
Two new species of the genus Haliplus Latreille, 1802 are described and illustrated: H. fiorentini sp. n. and H. regili sp. n., from Roraima state in northern Brazil, bringing the number of species known from Brazil to 14. The new species can be distinguished based on a series of characteristics, mainly observed in the elytra, prosternal and metaventral process, legs and male genitalia.